Communicating in Good Faith?: Dynamics of the Christian Right Agenda - Wilson, Angelia R. (Politics and religion, 2020)
It is an article of faith that organized interests represent members to elected officials making use of synchronized communication channels. Rarely, if at all, have researchers had access to multiple, internal, and external channels to test this notion. We mine a trove of nearly 2,500 emails the Family Research Council (FRC) sent to list subscribers from 2007 to 2018. Text tools allow us to depict message flexibility of the FRC. We then consider how internal and external messages may be linked by examining the issue content of emails in relation to press releases. Finally, we note the bills lobbied by FRC and the frequency these are mentioned in the internal email messages. Our findings are twofold. First, they support the conditional independence of communication channels in ways that appear to conform to the requisites of the different audiences: elected officials are likely mobilized by different signals than members are. Second, our evidence shows that the flexibility organized interests have in composing their communications can mean that different audiences are presented with considerably different political agendas. While FRC has significant sophisticated message flexibility, our data set indicates that such flexibility can raise serious concerns about good faith representation.